Association between GPS-based training load and injury risk in recreational runners: a large prospective study. - Cloosterman, Kyra L.A.; Vos, Robert-Jan de; Willemsen, Sten; Oeveren, Ben van; Visser, Edwin; Bierma-Zeinstra, Sita M.A.; Middelkoop, Marienke van (Journal of Athletic Training (KnowledgeWorks Global, Ltd), 2026)
Understanding the relationship between training load and injury in runners may provide information on how to reduce the risk of running injuries. To investigate the association between training load and injury risk in recreational runners with the use of Global Positioning System (GPS) data. Prospective cohort study. This study is part of a randomized-controlled trial on running injury prevention among recreational runners. Runners who provided informed consent received three follow-up questionnaires and were requested to share GPS data. Adult runners who registered for running events (distances 10-42.195 kilometers) in the Netherlands. GPS-based training load was calculated as Acute:Chronic Workload Ratio (ACWR) based on distance, duration, or speed of each training session. Cox regression models were performed to evaluate the association (Hazard Ratio; HR) between ACWR and running-related injury (RRI) onset. GPS data from 461 participants (72.9% men; mean(SD) age 43.8(12.4) years; 42.3% reported a new RRI during follow-up) were used for analyses with a total of 20,425 training sessions. A positive association between ACWR and RRI onset was found for distance (HR 1.32; 95%CI 1.00 to 1.74) and duration (HR 1.39; 95%CI 1.07 to 1.79). In the analyses adjusted for confounding variables only ACWR based on duration (HR 1.33; 95%CI 1.02 to 1.74) remained positively associated with RRI onset. No significant association was found between ACWR and RRI onset when excluding runners with an RRI at baseline (15.8%). We identified an association between ACWR and RRI onset in runners based on distance and duration respectively. The clinical relevance of the identified associations are questionable given the small HRs and inconsistency in outcomes which makes the role of general training load advice in the prevention of RRIs uncertain.